A systematic review of progranulin concentrations in biofluids in over 7, 000 people: Assessing the pathogenicity of GRN mutations and other influencing factors. (1st February 2022) - Swift, Imogen J.; Esteve, Aitana Sogorb; Heller, Carolin; Zetterberg, Henrik; Rohrer, Jonathan D.
Abstract: Background: Heterozygous mutations in the GRN gene are a major cause of genetic frontotemporal dementia (FTD), accounting for an estimated 5‐10% of all people with FTD. GRN encodes for progranulin, with mutations causing haploinsufficiency, and being associated with significantly lower concentrations of progranulin in biofluids in mutation carriers compared to controls. Method: We performed a search of the literature (up to December 2019) looking for publications reporting progranulin concentrations within serum, plasma or CSF in any medical condition including FTD and other forms of dementia. We then contacted all authors and asked if they were able to share anonymised data from their study including progranulin concentrations and clinical data including specific mutation if present, clinical diagnosis, age at onset of dementia, sex, and GRN rs5848 polymorphism. Data from 7, 071 people was collated and analysed. Result: Data on plasma progranulin concentrations measured using the Adipogen assay was available from 3, 265 cases. Variability in levels across 109 different GRN mutations was seen and when split into mutation groups, missense variants outside the signal peptide had significantly higher levels compared to all other groups, suggesting that these variants are unlikely to be pathogenic. We established a plasma progranulin cut‐off value of 74.8ng/µL between pathogenic GRN mutation carriers and non‐carriers. We found that the GRN rs5848 polymorphism also affected plasma progranulin levels, with the TT genotype associated with significantly lower levels than CC. Sex differences were also seen, with significantly higher progranulin levels in females than males. Conclusion: Together these findings highlight the variable pathogenicity of different GRN mutations and the importance of considering other factors such as genetic risk factors and sex differences when looking at biofluid concentrations of progranulin. This is of particular relevance in upcoming clinical trials of progranulin‐associated FTD where progranulin levels are being measured as outcome measures.